Legend of Ngarai Sianok: Interpreting the Legend of Ngarai Sianok through Program Music in a Post-Rock Composition - Putra, Syahrul Al Basyir; Marh, Fahmi (Kirana Publisher (KNPub), 2025)
Ngarai Sianok is a steep valley located on the border of Bukittinggi, IV Koto District, Agam Regency, West Sumatra, renowned for its legend that tells the conflict between Sang Sapurba and Katik Muno, two figures symbolizing greed and arrogance, ultimately leading to destruction. This legend contains profound values and serves as an interesting subject for interpretation through musical composition, aiming to depict the impact of negative human traits on societal harmony. This study seeks to interpret this legend through music. The method used in the creation of this work consists of four main stages: preparation, elaboration, synthesis, and conceptual realization. This approach involves in-depth musical exploration and creative expression through a composition based on the Post-rock genre, known for its atmospheric strength and intense of emotional expression. The composition is structured into three main sections representing the progression of the story: Emptiness. The result of this study is a musical composition that not only adapts traditional Minangkabau elements but also incorporates contemporary techniques within the Post-rock genre to create an ambiance that illustrates the contrast between harmony and destruction. Through the use of diverse instruments, this work seeks to convey the essence of the legend to the audience, providing a deeper understanding of the moral message regarding the consequences of human greed and arrogance. In conclusion, this composition does not merely narrate a legendary tale but also invites listeners to reflect on social and humanitarian values relevant to contemporary contexts.